Self-direction in adult undergraduates: Perceptions of learner control - Sally S Blowers (Adult Education Research Conference, 1993)
This exploratory case study employed qualitative interviews to examine selected aspects of self-directed learning as they were revealed within the context of the collegiate classroom.